Utilization of Suji Leaves Extract (Pleomele Angustifolia N.E Brown) in Inhibiting Carrageenan-Induced Inflammation on Rats - Reni Koja; Endang Prangdimurti; Puspo Edi Giriwono (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Suji leaf (Pleomele angustifolia N.E. Brown) has long been used as an ingredient for traditional medicines. This study seeks to evaluate the anti-inflammatory activity of suji leaf extract in terms of its ability to reduce oedema in the hind paws of rats. Six groups were treated: negative control, positive control given diclofenac sodium as anti-inflammatory medication, two groups of suji leaf extract powder (SEP) with doses of 300 and 800 mg/kg, acetone extract of suji leaf (AES), and a group of acetone extract of SEP (EA-SEP) at a dose of 500 mg/kg with oral administration. Injections of 1% carrageenan suspension into the right hind paw of rats induced inflammation. The results demonstrated that SEP administered at a dose of 800 mg/kg has an inflammatory capacity (80.56%), AES (56.94%), and AE-SEP (75.7%). Chlorophyll, total phenol, and antioxidant capacity in SEP (9.0809 mg /g sample; 3.7354 mg GAE/g sample; 3.04 mg AAE/g sample), AES (4.6471 mg /g sample; 0.9994 mg GAE/g sample; 3.26 mg AAE/g sample), and AE-SEP (6.4912 mg /g sample; 2.1703 mg GAE/g sample; 2.55 mg AAE/g sample). According to qualitative test results, Suji extract contains bioactive compounds of the flavonoid group, saponins, steroids, and triterpenoids. It is believed that phenolic compounds function as anti-inflammatory agents.